2011
DOI: 10.1007/s11106-011-9329-6
|View full text |Cite
|
Sign up to set email alerts
|

Selective laser sintering/melting of nitinol–hydroxyapatite composite for medical applications

I. V. Shishkovskii,
I. A. Yadroitsev,
I. Yu. Smurov

Abstract: The layer-by-layer synthesis of 3D parts from nitinol (NiTi intermetallide) and hydroxyapatite additions using selective laser sintering/melting (SLS/SLM) is studied. The effect of different laser parameters on the structure and phase composition of sintered/melted samples is analyzed with optical and scanning electron microscopy, x-ray diffraction, and energy-dispersive x-ray analysis. Optimum SLS/SLM parameters are determined for the synthesis of NiTi + HA to be used in tissue engineering and manufacture of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…There is also the possibility of preheating in SLM systems. This works either by setting an additional laser to preheat the powder to temperatures below its melting point [35] or to adjust the building table temperature to a commercially-available maximum of 300 • C [36]. SLM machines use argon atmosphere to prevent sample oxidation, but there is a possibility to perform a process in a controlled atmosphere to enhance the mechanical properties of fabricated material [37].…”
Section: Slm and Ebm Differencesmentioning
confidence: 99%
“…There is also the possibility of preheating in SLM systems. This works either by setting an additional laser to preheat the powder to temperatures below its melting point [35] or to adjust the building table temperature to a commercially-available maximum of 300 • C [36]. SLM machines use argon atmosphere to prevent sample oxidation, but there is a possibility to perform a process in a controlled atmosphere to enhance the mechanical properties of fabricated material [37].…”
Section: Slm and Ebm Differencesmentioning
confidence: 99%
“…For example, SLM has been used to manipulate NiTi properties by adding hydroxyapatite (an excellent bone bioactive material) to produce a composite for biomedical applications. 79 Furthermore, LMD has been utilized to produce a ductile and wear-resistant in situ TiB 2 /NiTi coating (to increase durability of Ti-6Al-4V alloy) from a powder mixture of Ni + TiB 2 + Ti 80 , 81 or even to generate a functionally graded Ti-NiTi to customize corrosion and mechanical behavior. 82 These are promising aspects that can potentially improve the effi ciency of functional components.…”
Section: Nonstandard Niti-based Alloys Made By Laser Am Methodsmentioning
confidence: 99%
“…2 Research efforts have been directed to the elimination of Ni release from the surface and therefore improving the corrosion resistance and as well as the biocompatibility of the implants. [1][2][3][4][5] Nickel is known for its diverse effects on human body, including allergic reactions and toxicity. 6 Studies on commercially available orthodontic wires showed increased Ni release rate with time of exposure and type of solution, indicating the need for better understanding the processes at the interface between the implant and biological environment.…”
Section: Introductionmentioning
confidence: 99%
“…2,7 Various surface modification techniques have been used including mechanical, chemical and thermal treatments, as well as bioactive coatings such as calcium phosphate coatings. 4,5,8,9 Hydroxyapatite coatings (HAP) are appropriate candidates for biocompatibility improvement since they offer an excellent surface for cell growth. 8,10 However, they cannot be used in load-bearing applications due to their poor mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation